Determination of Distribution Routes Using the Saving Matrix Method to Minimize Shipping Costs at PT. SUKUN TRANSPORT LOGISTICS - Febriyanti, Dian Erliana; Primadasa, Rangga; Bhakti Sutono, Sugoro (Spektrum Industri, 2022)
PT. Sukun Transport Logistics is a company engaged in shipping,logistics and also transportation vehicle rental services. Theproblems faced by PT. Sukun Transport Logistics is a lack oftransport vehicle capacity, causing the use of transport vehiclesthat are not suitable and the distribution of sub-routes is notbalanced. Therefore, to overcome these problems, it is necessaryto determine the optimal distribution route using the saving matrixmethod. The saving matrix method is a method to shortenmileage, estimate distribution time and minimize shipping costs atPT. Sukun Transport Logistics. From the results of the routeresearch in this study, it is known that the route proposal with thesaving matrix method opens 2 sub routes from the previous 3 subroutes, the total distance through the saving matrix method andthe closest calculation method is 299 km. While the total distanceof the actual route delivery to the company is 313 km. Thedistance saving of this research with the company's actual routeis 14 km or 4.47%. At the time of saving of 164 minutes or20.97%, and distribution cost savings of Rp. 141,658 or 25.53%.